New ideas for nursing - Greičienė, Svetlana (Slauga. Mokslas ir praktika, 2021)
The scholarship motivates nursing talent to become innovaters for healthcere deveplemn while building and promoting competence in profesional nursing. By lifting nursing talent and their ideas the project aims to increase the status nursing as a profession.